The Mediating Role of Work Loyalty in Relationship Between Professionalism on Employee Performance - Ja'is, Muhammad; Suyono, Joko; Elisabeth, Damarsari Ratnasahara (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: The purpose of this study is to analyze the influence of professionalism on employee performance, professionalism on work loyalty, and to analyze the mediating role of work loyalty. Design/methodology/approach: The sample in this study were 74 employes of regional drinking company owned by the regional government in East Kutai, Indonesia. Questionnaire was used to obtain the data and data analysis technique used was Partial Least Square (PLS). Findings: The results indicated that professionalism influences employee performance, professionalism influences work loyalty, and work loyalty is able to mediate the influence of professionalism on employee performance. Research limitations/implications: This research is limited to doing regional drinking company owned by the regional government in East Kutai, Indonesia. For generalization so that further research can be carried out in different organizations or companies and in different regions (cities). Practical implications: The results of this research can be used as a reference to improve employee performance in regional drinking company owned by the regional government and similar industries. Originality/value: The results of the research show that among the variables of professionalism and work loyalty need to be implemented in regional drinking company owned by the regional government and similar industries.